Food Inequality, Injustice, and Rights. (27th February 2019) - D'Odorico, Paolo; Carr, Joel A; Davis, Kyle F; Dell'Angelo, Jampel; Seekell, David A
Abstract: As humanity continues to grow in size, questions related to human rights and the existing unequal distribution of food resources have taken on greater urgency. Is inequality in food access unjust or a regrettable consequence of the geographic distribution of biophysical resources? To what extent are there obligations to redress inequalities in access to food? We draw from a human rights perspective to identify obligations associated with access to food and develop a quantitative framework to evaluate the fulfillment of the human right to food. We discuss the capacity of socioeconomic development to reduce inequalities in per capita food availability with respect to the distribution of biophysical resources among countries. Although, at the country level, international trade shows the capacity to reduce human rights deficits by increasing food availability in countries with limited food production, whether it actually improves the fulfillment of the right to food will depend on within-country inequality.